Single‐step antibiotic‐mediated synthesis of kanamycin‐conjugated gold nanoparticles for broad‐spectrum antibacterial applications. (27th June 2022) - Patil, T.; Khot, V.; Pandey‐Tiwari, A.
Abstract: Widespread and irrational use of antibiotics results in the development of antibiotic‐resistant bacteria. Thus, there is a need to develop novel antibacterial agents in order to replace conventional antibiotics and to increase the efficacy of already existing antibiotics by combining them with other materials. Herein, a single‐step antibiotic‐mediated synthesis of antibiotic‐conjugated gold nanoparticles is reported. In this single‐step method antibiotic Kanamycin, an aminoglycoside itself plays the role of reducing as well as capping agent by reducing gold salt into gold nanoparticles. The kanamycin‐conjugated gold nanoparticles (Kan‐AuNPs) were confirmed by UV–Visible spectroscopy and further physico‐chemically characterized by various instrumental techniques. Synthesized Kan‐AuNPs showed broad‐spectrum antibacterial activity against Gram‐positive Staphylococcus aureus as well as Gram‐negative Escherichia coli bacterial strains. They are also found to be effective against Pseudomonas aeruginosa and pathogenic E. coli isolated from urinary tract infections (UTIs) patients, which are responsible to cause hospital‐acquired infections like nosocomial, burn wound and UTIs. The minimum inhibitory concentration (MIC) of Kan‐AuNPs is 50 μg ml −1 for S. aureus and E. coli, 125 μg ml −1 for P. aeruginosa and 100 μg ml −1 for E. coli isolated from UTIs patients. It is also evident that the MIC of Kan‐AuNPs for antibacterial activity is lower as compared to antibiotic kanamycin alone for all bacterial strains. Hence, the one‐step strategy of synthesis for Kan‐AuNPs is a suitable strategy for fighting infectious bacterial strains in hospitals, healthcare and the pharmaceutical industry. Abstract : Significance and Impact of the Study: A low‐cost single‐step method of antibiotic‐mediated synthesis of kanamycin‐conjugated gold nanoparticles (Kan‐AuNPs), eliminating the use of reducing agents and capping agents is proposed. Kan‐AuNPs display broad‐spectrum antibacterial activity against Gram‐positive and Gram‐negative bacteria pathogens. Kan‐AuNPs show significant antibacterial activity against Pseudomonas aeruginosa and Escherichia coli strain isolated from patients suffering from urinary tract infections. The minimum inhibitory concentration of Kan‐AuNPs for antibacterial activity is lower as compared to antibiotic kanamycin alone for all tested bacterial strains.